2013
DOI: 10.1039/c3mb25383j
|View full text |Cite
|
Sign up to set email alerts
|

Secretome analysis of Glioblastoma cell line - HNGC-2

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive type of primary malignant tumor of the central nervous system. We have carried out a deep analysis of the secretome of a rapidly proliferating and tumorigenic cell line HNGC-2, representing GBM, in an effort to identify proteins, which may be targeted in the plasma of GBM patients as markers for diagnosis and disease surveillance. Prefractionation of the proteins from the conditioned medium of HNGC-2 cells in SDS gels followed by LC-MS/MS analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…SignalP (version 4.1, stringency 0.6) 4 (Petersen et al, 2011; Nielsen, 2017) observed 45 of these proteins having signals consistent with their production and export via the protein secretion pathway (Supplementary Table S1). Further inspection of our data using the Human Cancer Secretome Database (HCSD) 5 (Feizi et al, 2015) finds 98.8% (83/84) of C6/C6-13 proteins have been identified within the secretome of other cancers (Feizi et al, 2015); with 88% (74/84) observed with other GBM studies (Kashyap et al, 2010; Formolo et al, 2011; Gupta et al, 2013; Supplementary Table S1). Secretomes of both cell lines had strong functional links to Cellular Movement ( P = 2.15 × 10 -16 ), Cell Death and Survival (2.13 × 10 -15 ), Cancer (1.87 × 10 -12 ), and PTM (post-translational modification) (2.46 × 10 -11 ) (Figure 6A,C).…”
Section: Resultsmentioning
confidence: 93%
“…SignalP (version 4.1, stringency 0.6) 4 (Petersen et al, 2011; Nielsen, 2017) observed 45 of these proteins having signals consistent with their production and export via the protein secretion pathway (Supplementary Table S1). Further inspection of our data using the Human Cancer Secretome Database (HCSD) 5 (Feizi et al, 2015) finds 98.8% (83/84) of C6/C6-13 proteins have been identified within the secretome of other cancers (Feizi et al, 2015); with 88% (74/84) observed with other GBM studies (Kashyap et al, 2010; Formolo et al, 2011; Gupta et al, 2013; Supplementary Table S1). Secretomes of both cell lines had strong functional links to Cellular Movement ( P = 2.15 × 10 -16 ), Cell Death and Survival (2.13 × 10 -15 ), Cancer (1.87 × 10 -12 ), and PTM (post-translational modification) (2.46 × 10 -11 ) (Figure 6A,C).…”
Section: Resultsmentioning
confidence: 93%
“…These interconnected glycolytic proteins catalyze the conversion of glucose to generate ATP, NADH, and pyruvate molecules to support the high load of anabolic reaction in cells. Overexpression of these proteins in the secretome of a glioblastoma cell line was associated with the progression of glioblastoma (Gupta et al, 2013). Li et al (2019) also showed that the growth and the progression of SH-SY5Y cells were significantly reduced following treatment with glycolysis inhibitory peptide.…”
Section: Discussionmentioning
confidence: 94%
“…SERPINI1 promote the mechanism for the initiation of brain metastasis in lung and breast cancers, by guarding tumor cells from death signals and promoting vascular cooption (Valiente et al 2014). Other members of this family are also involved in GBM pathogenesis; where SERPINE1 showed decreased expression in GBM cells (Tarassishin et al 2014), whereas SERPINA4, SERPINA10, SERPINC1 and SERPINF1 proteins exhibit signi cant downregulation in plasma of GBM patients (Gautam et al 2012;Gupta et al 2013). A strong interaction is evident for SERPINI1 with myc proto-oncogene protein (MYC) and protein max (Max), two prominent oncoproteins (Fig.…”
Section: Discussionmentioning
confidence: 99%